Association of the neutrophil-to-lymphocyte ratio with sudden cardiac death in the patients with diabetic foot ulcer - Chen, Yi; Zhao, Junyan; Sun, Yuchen; Yang, Zhongjing; Yang, Caizhe; Zhu, Di (Frontiers in Endocrinology, 2025)
AimsThis study aims to investigate the relationship between the neutrophil-to-lymphocyte (NLR) and the risk of sudden cardiac death (SCD) in the patients with diabetic foot ulcer (DFU).MethodsA retrospective study enrolled 688 patients with DFU who were admitted to Air Force Medical Center between January 2010 and December 2023. To control for potential confounding effects, a 1:1 propensity score matching (PSM) method was applied. The relationship between NLR and SCD risk was analyzed using the Kaplan-Meier (K-M) survival curve analysis, multivariate Cox proportional hazard regression model, Restricted cubic spline (RCS) model analysis and subgroup analyses.ResultsOver a median follow-up period of 61 months, 38 cases of SCD were documented. Based on median NLR, participants were stratified into lower (<4.22) and higher (≥4.22) NLR groups. Cox proportional hazard model revealed that individuals with higher NLR was independently associated with the increased risk of SCD (HR: 3.64, 95% CI: 1.21 ~ 10.91, P=0.021). RCS model showed that SCD risk was non-linearly correlated with gradual increases in NLR levels. Subgroup analyses confirmed the stability of the results.ConclusionsElevated NLR independently confers an increased risk for SCD in individuals with DFU.